2020
DOI: 10.1155/2020/8672850
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, HIV, and Immune Quiescence: Leveraging on Immunomodulatory Products to Reduce HIV Susceptibility

Abstract: The relationship between inflammation and HIV has been a focus of research over the last decade. In HIV-infected individuals, increased HIV-associated immune activation significantly correlated to disease progression. While genital inflammation (GI) has been shown to significantly increase the risk of HIV acquisition and transmission, immune correlates for reduced risk remain limited. In certain HIV-exposed seronegative individuals, an immune quiescent phenotype characterized reduced risk. Immune quiescence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 265 publications
(197 reference statements)
0
8
0
Order By: Relevance
“…In this study, dietary GML effectively benefited the jejunal MUC 2 content and up-regulated ZO-1 and occludin expression, demonstrating the beneficial effect of GML on intestinal barrier of broilers. The TNF-α and IFN-γ are related to the reduction in epithelial barrier function and increases the permeability of the mucosal barrier ( 35 ). The reduction in serum TNF-α level and decrease in jejunal IFN-γ expression in this study supported the idea that GML mediates intestinal barrier function through a mechanism associated with the attenuation of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dietary GML effectively benefited the jejunal MUC 2 content and up-regulated ZO-1 and occludin expression, demonstrating the beneficial effect of GML on intestinal barrier of broilers. The TNF-α and IFN-γ are related to the reduction in epithelial barrier function and increases the permeability of the mucosal barrier ( 35 ). The reduction in serum TNF-α level and decrease in jejunal IFN-γ expression in this study supported the idea that GML mediates intestinal barrier function through a mechanism associated with the attenuation of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dietary GML effectively benefited the jejunal muc 2 content and up-regulated ZO-1 and occludin expression, demonstrating the beneficial effect of GML on intestinal barrier of broilers. The TNF-α and IFN-γ are related to the reduction in epithelial barrier function and increases the permeability of the mucosal barrier (31). The reduction in serum TNF-α level and decrease in jejunal IFN-γ expression in this study supported the idea that GML mediates intestinal barrier function through a mechanism associated with the attenuation of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dietary GML effectively benefited the jejunal muc 2 content and up-regulated ZO-1 and occludin expression, demonstrating the beneficial effect of GML on intestinal barrier of broilers. The TNF-α and IFN-γ are related to the reduction in epithelial barrier function and increases the permeability of the mucosal barrier (31).…”
Section: One Of the Central Ways Feed Compounds Affect Immunity Is Activating Nf-κbmentioning
confidence: 99%
“…However, the same group later carried out a randomized placebo-controlled trial, and found that aspirin treatment for 12 weeks resulted in no major impact on soluble CD14, IL-6, soluble CD163, d -dimer, T-cell, or monocyte activation, suggesting that inhibition of COX-1-mediated platelet activation may not significantly improve HIV-1-related immune activation [21] . Interestingly, daily low-dose aspirin was developed as an approach to decrease HIV-1 target cells at the female genital tract through systemic and local inflammation reduction, and preliminary results showed this may reduce HIV-1 susceptibility and become a novel HIV-prevention approach in low-risk women [22,23] …”
Section: Aspirinmentioning
confidence: 99%